Use of Chemical Flocculation and Nested PCR for Heterodera glycines Detection in DNA Extracts from Field Soils with Low Population Densities - Baidoo, Richard (Plant disease, 2017)
The soybean cyst nematode (SCN) Heterodera glycines is a major pathogen of soybean worldwide. Distinction between SCN and other members of the H. schachtii sensu stricto group based on morphology is a tedious task. A molecular assay was developed to detect SCN in field soils with low population densities and to differentiate SCN from other species. Various numbers of SCN eggs or juveniles were inoculated into 10 g of sterilized soil from which soil DNA was extracted using the PowerSoil DNA Isolation Kit. A specific amplicon was amplified using published SCN-specific primers SCNF1/SCNR1. This primer set was evaluated for the first time to detect SCN directly in soil DNA extracts. The specificity of the primers was confirmed by testing 36 isolates of other nematode species. The PCR assay detected one SCN egg or juvenile added to 10 g of soil. The assay was validated using 35 field soil samples. Grinding the field soil coupled with PCR inhibitor removal by AlNH4(SO4)20.12H2O treatment of soil DNA extracts followed by nested PCR enabled SCN detection as low as 12 SCN eggs/200 g soil. The PCR assay not only provides a sensitive method for SCN detection at low densities but also provides a discrimination method for SCN from other closely related nematodes